(untitled) (Research, Society and Development, 2022)
In order to analyze the publications about the use of sugarcane straw to increase the generation of electricity in the mills, the objective of this work is to present a set of works published between the years 2016 and 2020 on the subject to carry out an analysis of the technologies developed in this period. For this, a search was carried out in the Science Direct, Scopus and Web of Science databases, where, from search strings to select works considering theme and year of publication, 1738 published articles were found. In view of this result, the Start software was used to apply selection criteria for choosing the articles to be used in the systematic review. After performing all the steps of selection of the works in the software, only 18 articles were selected for reading the abstracts and of these, only 7 articles present studies on the use of straw for the generation of electric energy. A complete reading of these 7 articles was carried out and the working methods and results obtained by the authors are presented, thus enabling an analysis of the technologies researched throughout the study period.